(untitled) (Dhaka University Journal of Science, 2013)
9´-Desmethylgaruganin I has been isolated from the dichloromethane extract of the stem bark of Garuga pinnata Roxb. The crude extract was screened for antimicrobial activity against a wide range of gram-positive and gram-negative bacteria and fungi by disc diffusion method and cytotoxicity by brine shrimp lethality bioassay. The dichloromethane extract showed moderate inhibitory activity to microbial growth and weak cytotoxicity having LC90 25.703?g-mL1 DOI: http://dx.doi.org/10.3329/dujs.v61i2.17058 Dhaka Univ. J. Sci. 61(2): 131-134, 2013 (July)